2021
DOI: 10.1038/s41533-021-00235-x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices of patients and healthcare professionals regarding oral health and COPD in São Paulo, Brazil: a qualitative study

Abstract: Poor oral health is associated with worse clinical outcomes in Chronic Obstructive Pulmonary Disease (COPD). This qualitative study aimed to investigate the knowledge, attitudes and practices of COPD patients and primary health care professionals (HCPs) in Brazil - where there are high rates of COPD and periodontal disease. Semi-structured interviews with COPD patients (n = 9) and three semi-structured focus groups with HCPs (n = 25) were conducted in São Paulo. Interviews were thematically analysed using The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In this study, a qualitative research design was employed to gain a comprehensive understanding of OHCPs' views on obesity screening and management in dental settings [32]. The qualitative research method is a frequently used approach to explore complex social phenomena as well as to collect in-depth information on health professionals' experiences, views, and understanding on a wide range of topics [33][34][35]. The flexibility of the qualitative research design also allowed for simultaneous data collection and data analysis, as well as further investigation and analysis of the emerging themes [33].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, a qualitative research design was employed to gain a comprehensive understanding of OHCPs' views on obesity screening and management in dental settings [32]. The qualitative research method is a frequently used approach to explore complex social phenomena as well as to collect in-depth information on health professionals' experiences, views, and understanding on a wide range of topics [33][34][35]. The flexibility of the qualitative research design also allowed for simultaneous data collection and data analysis, as well as further investigation and analysis of the emerging themes [33].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported varying but low COPD awareness rates. The lowest was found in an Indian survey that included over 6000 participants from urban cities and reported 0.9% COPD awareness rate [ 23 ], whereas it was 4% in Brazil [ 22 , 24 ], 8% in France [ 25 ], 10% in Germany [ 22 ], 17% in Spain [ 26 ] and Canada [ 27 ], and 21.3% in Japan [ 28 ]. Although the current study demonstrated relatively higher rate of COPD awareness (23.13%) in Saudi Arabia, there is still a significant gap of knowledge, particularly among those aged 41–50 years old [OR: 0.58 (0.49 to 0.76)] and 51–60 years old [OR: 0.69 (0.56 to 0.84)], despite being at a greater risk of developing COPD [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis that COPD and periodontal disease are causally related and that treating one might affect the severity and progression of the other is supported, to some extent, by the available evidence [ 16 ]. However, Riley et al found that healthcare providers did not always understand the relationship between oral health and COPD [ 17 ]. This review will discuss the relationship between the two diseases and suggest future research directions.…”
Section: Introductionmentioning
confidence: 99%